Copepod response to ocean acidification in a low nutrient-low chlorophyll environment in the NW Mediterranean Sea. (15th February 2017) - Zervoudaki, S.; Krasakopoulou, E.; Moutsopoulos, T.; Protopapa, M.; Marro, S.; Gazeau, F.
Abstract: In order to identify how ocean acidification will influence biological interactions and fluxes among planktonic organisms and across trophic levels, a large-scale mesocosm experiment was performed in the oligotrophic Northwestern Mediterranean Sea in the framework of the European MedSeA project. Nine mesocosms were deployed in the Bay of Calvi (Corsica, France) in summer 2012. Six mesocosms were subjected to different levels of CO2 partial pressures ( p CO2 ; 550, 650, 750, 850, 1000 and 1250 μatm) covering the range of atmospheric p CO2 anticipated for the end of this century depending on future emission scenarios, and the last three mesocosms were unaltered (ambient p CO2 of ∼450 μatm). During this 21-day experiment, we monitored copepod egg and naupliar stocks, estimated copepod ( Acartia clausi and Centropages typicus ) feeding rates and determined the abundance and taxonomic composition of the mesozooplankton community at the start and at the completion of the experiment. This community was clearly dominated by copepods and its final composition slightly varied between mesocosms most likely due to natural and experimental variability that cannot be related to CO2 conditions. The abundances of eggs and nauplii as well as feeding rates of A. clausi and C. typicus on diatoms, dinoflagellates and ciliates showed no significant differences among CO2 levels. The above findings suggest that the experimental set-up especially for the specific trophic conditions and the short duration of the experiment did not provide the information on the effect of acidification that was expected. The acidification might have an effect on planktonic communities and even worsen the problems imposed by food limitation, therefore on this short time scale experiment and under the extreme ologotrophic conditions the signal that dominates was the food limitation. Highlights: Mesozooplankton composition, copepod egg and naupliar stocks as well as feeding performance were investigated. Ocean acidification does not have detectable effects on the studied parameters. Food limitation had more significant effect on copepods than ocean acidification. The experimental set-up for the oligotrophic conditions did not provide the information on the effect of acidification.